KARAKTERISASI MORFOLOGI VARIETAS JAGUNG KETAN DI KECAMATAN AMPANA KOTA KABUPATEN TOJO UNA-UNA - Yusran Yusran; Maemunah Maemunah (Universitas Tadulako, 2011)
The research aimed at inventing glutinous corn cultivar through collecting, characterizing and identifying various characters of clustering glutinous corn cultivars found in the villages of Tombuo, Padang, Sansarino and Uentanaga, Ampana Kota sub district of Tojo Una-Una district. The research was conducted between January and March 2010. The research applied a Survey Method and Observations in which the research site was decided based on the information gathered from Department of Agriculture, Plantation, Animal Husbandry and Animal Health of Tojo Una-Una district. Plant, cob and seed morphological characters were observed in order to determine the morphological diversity among the cultivars tested. Dendogram analysis was applied for identifying the similarities among the tested corn cultivars. The research findings showed that there are three different cultivar groups of glutinous corns with regard to their morphological characteristics in Kecamatan Ampana Kota. Key Words: Cluster, cultivar, dendrogram, glutinous Corn, morphology.